New Onset of Constipation during Long-Term Physical Inactivity: A Proof-of-Concept Study on the Immobility-Induced Bowel Changes - Iovino, Paola; Chiarioni, Giuseppe; Bilancio, Giancarlo; Cirillo, Massimo; Mekjavic, Igor B.; Pisot, Rado; Ciacci, Carolina (PLOS ONE, 2013)
BackgroundThe pathophysiological mechanisms underlining constipation are incompletely understood, but prolonged bed rest is commonly considered a relevant determinant. AimsOur primary aim was to study the effect of long-term physical inactivity on determining a new onset of constipation. Secondary aim were the evaluation of changes in stool frequency, bowel function and symptoms induced by this prolonged physical inactivity. MethodsTen healthy men underwent a 7-day run-in followed by 35-day study of experimentally-controlled bed rest. The study was sponsored by the Italian Space Agency. The onset of constipation was evaluated according to Rome III criteria for functional constipation. Abdominal bloating, flatulence, pain and urgency were assessed by a 100mm Visual Analog Scales and bowel function by adjectival scales (Bristol Stool Form Scale, ease of passage of stool and sense of incomplete evacuation). Daily measurements of bowel movements was summarized on a weekly score. Pre and post bed rest Quality of Life (SF-36), general health (Goldberg’s General Health) and depression mood (Zung scale) questionnaires were administered. ResultsNew onset of functional constipation fulfilling Rome III criteria was found in 60% (6/10) of participants (p=0.03). The score of flatulence significantly increased whilst the stool frequency significantly decreased during the week-by-week comparisons period (repeated-measures ANOVA, p=0.02 and p=0.001, respectively). Stool consistency and bowel symptoms were not influenced by prolonged physical inactivity. In addition, no significant changes were observed in general health, in mood state and in quality of life at the end of bed rest ConclusionsOur results provide evidence that prolonged physical inactivity is relevant etiology in functional constipation in healthy individuals. The common clinical suggestion of early mobilization in bedridden patients is supported as well.